The Impact of Stress at Work on Employeeâs Psychological Well-being in Jakarta - Kurnia, Nafiri Paramitha (iBuss Management, 2015)
Higher work demands is experienced by employees working in Jakarta due to companiesâ need to increase their productivity. Despite increasing productivity, higher work demands leads to higher stress at work, which indirectly affect companiesâ productivity itself. This research is conducted to study the extent of stress at work, along with its factors, in impacting employeeâs psychological well-being. Samples are employees working inÂ Jakarta from diverse industries, which are taken using questionnaire based on simple random sampling method, and 108 respondents are able to be obtained. Data is analyzed using Multiple Linear Regression, and the result there is significant impact of stress at work on employeeâs psychological well-being in Jakarta. The result also shows that Influence over Decision, Role Clarity, Autonomy and Control, and Peer Support are the factors of stress at work which significantly impact employeeâs psychological well-being.Keywords: Stress at work, job stressors, employeeâs psychological well-being Â